PERANCANGAN SISTEM PENGOLAHAN DATA PADA SMA NEGERI 6 KABUPATEN TEBO - Mahyuni Mahyuni; Sharipuddin Sharipuddin; Martono Martono (LPPM Universitas Dinamika Bangsa, 2014)
SMAN 6 Kabuapten Tebo is a school that specializes in secondary education. Data processing is still done manually by the analysis, causing problems that may require considerable time and frequent errors and calculation values ​​result in slow information to parties - those in need. The purpose of this study is to analyze the current system, in order to solve the problem - a problem faced by SMAN 6 Tebo by designing a data processing system academic applications that can generate the required data accurately in the submission of the report to the principal. Development of systems using the waterfall model, the implementation of this study using Visual Basic. Net 2008 and Microsoft Access 2007 and generate data processing applications that are expected to facilitate the administration of the data processing and report generation. Keywords: Design, Data Processing, Academic, Microsoft Visual Basic 2008